2023
DOI: 10.3390/bs13030206
|View full text |Cite
|
Sign up to set email alerts
|

From Academic Resilience to Academic Burnout among International University Students during the Post-COVID-19 New Normal: An Empirical Study in Taiwan

Abstract: (1) Background: In the context of the COVID-19 pandemic, it is imperative for higher education institutions to understand the socio-psychological issues of international students, a potentially vulnerable population on campuses, to assist them in pursuing their academic path while maintaining their psychological well-being. The objectives of this study were to determine the prevalence of academic burnout among international university students in Taiwan during the new normal and to explore the protective role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
2
0
2
Order By: Relevance
“…In 2020, 2021, and 2022 domestic students presented higher resilience levels than international students. Because resilience isa protective factor for the severity of anxiety and depression among university students [ 18 , 36 ], and also for academic burnout among international students in the so-called authors’ “post-COVID-19 new normal (Fall semester 2022–2023)” [ 41 ], these results could be related to the higher levels of depressive symptoms among international students.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, 2021, and 2022 domestic students presented higher resilience levels than international students. Because resilience isa protective factor for the severity of anxiety and depression among university students [ 18 , 36 ], and also for academic burnout among international students in the so-called authors’ “post-COVID-19 new normal (Fall semester 2022–2023)” [ 41 ], these results could be related to the higher levels of depressive symptoms among international students.…”
Section: Discussionmentioning
confidence: 99%
“…En relación con la ineficiencia y las evaluaciones hechas, los estudiantes manifiestan padecerlo en un nivel alto a medio, a causa de la inseguridad de terminar su carrera técnico profesional, dada a las problemáticas académicas, pedagógicas, institucionales y de gestión técnicaproductiva que repercuten de forma directa en su formación integral, tal como lo sugiere Wolters et al (2023). Esta relación llega hasta el extremo de crear un estado de confusión, y cursantes han llegado a solicitar cambio de sede, traslado interno a otra especialidad, y también con consecuencias externas como el convalidar sus estudios en otra institución, la cual podría proveerles mayor seguridad y confianza (Tran et al, 2023).…”
Section: Discussionunclassified
“…A partir de lo descrito, se precisa intervenciones psicoeducativas (IP) con temáticas que difundan la autocompasión, resiliencia y la satisfacción por los objetivos de vida conseguidos (Charbonnier et al, 2023;Shin et al, 2023;Tran et al, 2023) procurando la revalorización del bienestar general de las personas como entidades únicas e importantes (Chirkowska-Smolak et al, 2023;Andrade et al, 2023).…”
Section: Introductionunclassified
“…The study concluded that addressing academic burnout is crucial for fostering student participation in the class. The research carried out by Tran et al (2023) aims to understand the prevalence of academic burnout among international university students in Taiwan during the post-COVID-19 new normal and explore the preventive measures of academic resilience. MBI-SS and the Student Resilience Survey (SRS) were used to collect data from 383 foreign university students.…”
Section: Past Studies On Burnout Among Learnersmentioning
confidence: 99%